Exploring the Interplay of Job Satisfaction, Work Motivation, and Organizational Commitment on Service Quality: Evidence from Café Employees in Kediri, Indonesia - Vidyasana Viveka Vira Paksi Putri Vientya; M. Shohibul Jamil; Mohamad Sodikin (E-logis : Jurnal Ekonomi Logistik, 2025)
The purpose of this study is to examine how organizational commitment, work motivation, and job satisfaction affect the level of service provided by café workers in Kota District, Kediri, East Java. The whole population of 75 employees from seven cafes who were sampled using census methodologies were surveyed as part of this quantitative investigation. A five-point Likert scale questionnaire was used to collect data, and the SPSS software was used to analyze the data using multiple linear regression, validity, reliability, t-test, F-test, and coefficient of determination (R2). The findings demonstrated that, both partially and concurrently, three independent variables job satisfaction, work drive, and organizational commitment had a favorable and significant impact on service quality. Of the three, organizational commitment had the most impact on service quality (β = 0.529), indicating that employee sense of responsibility, loyalty, and emotional attachment are important factors in providing excellent service. These results support the findings of worldwide research indicating organizational commitment is the primary determinant of service behavior in the service sector and are consistent with Meyer and Allen's (1997) notion of affective commitment. This study's contribution is found in the micro context of Indonesian café enterprises, which demonstrates that increasing staff dedication and engagement at work is a key tactic for raising customer service quality.